Mediating Effect of Inflation on the Relationship between Financial Performance and Share Value of Listed Deposit Money Banks in Nigeria - Mohammed Saleh; Muhammad Shettima Daluma (CV. Kalimasada Group, 2025)
In recent times, inflation in Nigeria has been on the rise, with the inflation rate reaching 34.80% in December 2024, up from 34.60% in November 2024. This increase of 0.20% can largely be attributed to seasonal demand pressures, particularly during the festive period, which further exacerbates the cost of goods and services in the economy. This study aims to investigate the mediating effect of inflation on the relationship between financial performance and share value of the listed Deposit Money Banks in Nigeria. The study adopts a quantitative research approach based on the positivist research paradigm using panel secondary data from 10 Nigerian banks for the period 2015–2024. Financial performance is proxied by Return on Equity (ROE) and Earnings per Share (EPS), while share value represents the dependent variable. Panel data regression analysis is employed to examine the mediating role of inflation in the relationship between financial performance and share value. The results indicate that inflation significantly mediates the relationship between financial performance and share value. The findings reveal that during periods of inflation, the effect of higher return on equity on share value is strengthened, which is consistent with the adaptive strategic response theory. These results highlight the need for adaptive strategies in Nigerian banking practices. Therefore, policymakers and bank managers should focus on effective inflation management strategies to mitigate its adverse effects on share values, particularly during periods of high inflation.